Polityka władz polskich wobec ludności niemieckiej w okresie funkcjonowania Ministerstwa Ziem Odzyskanych. - Kacprzak, Paweł (Wydawnictwo Poznańskie sp. z o.o., 2010)
The German population living within the Polish territorial boundaries after the end of the Second World War was subjected to certain policy and state activities. The fundamental objective of the Polish authorities, resulting from the right of state, the social reality of the time and the national policy adopted by the government, was to displace the Germans from the territory of Poland. When the Ministry for Regained Territories was still in power, a number of actions were taken to ‘encourage’ the Germans to leave as well as to prevent them from associating or forming organisations. Such actions were possible because the Germans who lived in Poland at that time were practically deprived of any legal protection. When the Ministry for Regained Territories was about to discontinue its activity at the wake of the Stalinisation of the Polish state, those nationalistic attitudes weakened.
POLICY OF POLISH AUTHORITIES TOWARDS GERMAN POPULATION UNDER THE MINISTRY FOR REGAINED TERRITORIES.
Keywords: Historia Polski; Ustrój Polski; Ministerstwo Ziem Odzyskanych; Ludność niemiecka